Application of a proton microprobe to study diffusion profiles of Ce in synthetic aluminosilicates - Bondarenko, V.N.; Goncharov, A.V.; Kuz’menko, V.V.; Pistryak, V.M.; Saenko, S.Yu.; Sukhostavets, V.I.; Surkov, A.E. (Вопросы атомной науки и техники, 2005)
The procedure of measuring the diffusion profiles of Cerium by means of a proton microprobe was developed. These profiles in the synthetic aluminosilicate matrix synthesized on the base of kaolin and red granite were measured Відпрацьованo методику виміру дифузійних профілів Ce за допомогою протонного мікрозонда і проведено вимірювання таких профілів у синтетичній алюмосилікатній матриці, синтезованої на основі каоліну і червоного граніту. Отработана методика измерения диффузионных профилей Ce с помощью протонного микрозонда и проведено измерение таких профилей в синтетической алюмосиликатной матрице, синтезированной на основе каолина и красного гранита